Effects of cold water immersion and contrast water therapy for recovery from team sport: A systematic review and meta-analysis - Higgins, T. R.; Greene, D. A.; Baker, M. K. (The Journal of Strength and Conditioning Research, 2017)
To enhance recovery from sport, cold water immersion (CWI) and contrast water therapy (CWT) have become common practice within high level team sport. Initially, athletes relied solely on anecdotal support. As there has been an increase in the volume of research into recovery including a number of general reviews, an opportunity existed to narrow the focus specifically examining the use of hydrotherapy for recovery in team sport. A Boolean logic [AND] keyword search of databases was conducted: SPORTDiscus; AMED; CINAHL; MEDLINE. Data were extracted and the standardized mean differences were calculated with 95% confidence interval (CI). The analysis of pooled data was conducted using a random-effect model, with heterogeneity assessed using I2. Twenty-three peer reviewed articles (n = 606) met the criteria. Meta-analyses results indicated CWI was beneficial for recovery at 24 hours (countermovement jump: p = 0.05, CI: -0.004 to 0.578; All-out sprint: p = 0.02, -0.056 to 0.801) following team sport. The CWI was beneficial for recovery at 72 hours (fatigue: p = 0.03, CI: 0.061-1.418) and CWT was beneficial for recovery at 48 hours (fatigue: p = 0.04, CI: 0.013-0.942) following team sport. The CWI was beneficial for neuromuscular recovery 24 hours following team sport, whereas CWT was not beneficial for recovery following team sport. In addition, when evaluating accumulated sprinting, CWI was not beneficial for recovery following team sports. In evaluating subjective measures, both CWI (72 hours) and CWT (24 hours) were beneficial for recovery of perceptions of fatigue, following team sport. However neither CWI nor CWT was beneficial for recovery, of perceptions of muscle soreness, following team sport.